DNA Vaccines Against Mycoplasma Elicit Humoral Immune Responses in Ostriches - Wium, Martha; Jonker, Hester Isabella; Olivier, Adriaan Jacobus; Bellstedt, Dirk Uwe; Botes, Annelise (Frontiers in Immunology, 2019)
In ostriches, the population densities resulting from intensive rearing increases susceptibility to pathogens such as mycoplasmas. In addition to good management practices, vaccination offers an attractive alternative for controlling mycoplasma infections in food animals, instead of using antibiotics, which often leave unacceptable residues. The use of live attenuated vaccines, however, carry the concern of reversion to virulence or genetic recombination with field strains. Currently there are no commercially available vaccines against ostrich-infecting mycoplasmas and this study therefore set out to develop and evaluate the use of a DNA vaccine against mycoplasma infections in ostriches using an OppA protein as antigen. To this end, the oppA gene of “Mycoplasma nasistruthionis sp. nov.” str. Ms03 was cloned into two DNA vaccine expression vectors after codon correction by site-directed mutagenesis. Three-month-old ostriches were then vaccinated intramuscularly at different doses followed by a booster vaccination after six weeks. The ability of the DNA vaccines to elicit an anti-OppA antibody response was evaluated by ELISA using the recombinant OppA protein of Ms03 as coating antigen. A statistically significant anti-OppA antibody response could be detected after administration of a booster vaccination indicating that the OppA protein was successfully immunogenic. The responses were also both dose and vector dependent. In conclusion, the DNA vaccines were able to elicit an immune response in ostriches and can therefore be viewed as an option for the development of vaccines against mycoplasma infections.